How Do Floridians Perceive their Role in Protecting Water Quality and Quantity through Landscape Practices? - Laura A. Sanagorski Warner; Alexa J. Lamm; Anil Kumar Chaudhary (EDIS)
Florida is faced with challenges in protecting both water quality and quantity; the state’s incredible number of home landscapes can positively or negatively impact water depending on how landscapes are managed. In 2016, Florida residents with irrigated landscapes were surveyed in order to create more effective Extension programs regarding landscape best management practices. This 4-page document discusses the results of this survey. Written by Laura A. Sanagorski Warner, Alexa J. Lamm, and Anil Kumar Chaudhary and published by the UF/IFAS Department of Agricultural Education and Communication, January 2018. http://edis.ifas.ufl.edu/wc293